Modifikasi Mesin Pemotong Rumput Menjadi Alat Panen Sawit Mekanik - Romiyadi, Romiyadi; Swasono, Tulus (Jurnal Sains dan Ilmu Terapan, 2018)
Oil palm harvesting is the process of cutting the palm fruit bunches from the tree to transporting them to the mill which includes the activities of cutting the ripe fruit bunches, picking loose fruit, cutting the fronds, transporting the produce to TPH, and transporting the produce to the mill (PKS). Most of the oil palm farmers use conventional equipment in harvesting oil palm fruit such as dodos or egrek. The process of harvesting oil palm using dodos or egrek will consume a lot of energy because the process is quite difficult and the tools are quite heavy and the equipment is still conventional. This mechanical oil harvesting tool is designed and made to help and facilitate oil palm farmers in carrying out oil palm harvesting.